Site-Selective Antibody Functionalization via Orthogonally Reactive Arginine and Lysine Residues. Issue 9 (19th September 2019) - Hwang, Dobeen; Nilchan, Napon; Nanna, Alex R.; Li, Xiaohai; Cameron, Michael D.; Roush, William R.; Park, HaJeung; Rader, Christoph
Summary: Homogeneous antibody-drug conjugates (ADCs) that use a highly reactive buried lysine (Lys) residue embedded in a dual variable domain (DVD)-IgG1 format can be assembled with high precision and efficiency under mild conditions. Here we show that replacing the Lys with an arginine (Arg) residue affords an orthogonal ADC assembly that is site-selective and stable. X-ray crystallography confirmed the location of the reactive Arg residue at the bottom of a deep pocket. As the Lys-to-Arg mutation is confined to a single residue in the heavy chain of the DVD-IgG1, heterodimeric assemblies that combine a buried Lys in one arm, a buried Arg in the other arm, and identical light chains, are readily assembled. Furthermore, the orthogonal conjugation chemistry enables the loading of heterodimeric DVD-IgG1s with two different cargos in a one-pot reaction and thus affords a convenient platform for dual-warhead ADCs and other multifaceted antibody conjugates. Graphical Abstract: Highlights: X-ray crystallography confirmed an engineered antibody with a reactive arginine The reactive arginine enabled site-selective and stable antibody functionalization Pairing reactive arginine and lysine facilitated orthogonal dual cargo conjugation The platform was applied to antibody-drug conjugates in dual variable domain format Abstract : Hwang, Nilchan et al. convert a reactive lysine in a catalytic antibody to a reactive arginine, reveal its location by X-ray crystallography, and utilize the engineered antibody for site-selective antibody functionalization including its pairing with the original antibody for orthogonal dual cargo conjugation.